Analisis Penyebaran Hoaks COVID-19 di Indonesia - Endang Indartuti; Indah Murti; Kusnan Kusnan (Society, 2024)
In Indonesia, social media is considered one of the primary channels for the massive spread of hoaxes related to the COVID-19 pandemic. The spread of hoaxes through social media is difficult to control due to the rapid advancement of internet-based information technology and the low level of digital literacy among the public. This study aims to analyze the dissemination of hoaxes and the keywords frequently associated with COVID-19 hoaxes in Indonesia from 2020 to 2022. Employing a descriptive qualitative research approach, this study uses non-participant observation on the website turnbackhoax.id as the data collection method and applies an interactive model for data analysis. The findings reveal that COVID-19 hoaxes in Indonesia are predominantly classified into misleading content, false context, and fabricated content, with fabricated content being identified as the most dangerous type.